Pengembangan Media Kartu Domino Modifikasi Pada Pembelajaran Tematik di Sekolah Dasar - Zaeni, Abu; Ngainun Na’ima, Alfin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This research develops a modified domino card learning media as a new innovation to enhance students' understanding in Thematic learning for Grade III at SDN Kebonrejo 1 Kepung Kediri, specifically Theme 8